2020
DOI: 10.48550/arxiv.2003.03494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outdoor mmWave Base Station Placement: A Multi-Armed Bandit Learning Approach

Abstract: Base station (BS) placement in mobile networks is critical to the efficient use of resources in any communication system and one of the main factors that determines the quality of communication. Although there is ample literature on the optimum placement of BSs for sub-6 GHz bands, channel propagation characteristics, such as penetration loss, are notably different in millimeter-wave (mmWave) bands than in sub-6 GHz bands. Therefore, designated solutions are needed for mmWave systems to have reliable quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…• Objective Function: The objective of the process is to find the IRS-ASA pairs that maximizes the average rates throughout the drone corridor, where ξ is the cardinality of ASA set, [U], and R u,µ is the channel rate from (5), achieved when all the IRSs in subset-µ serve the u th ASA. A higher s max yields increased computational complexity; however, this is not a concern as the optimization process runs offline and the IRSs are placed only once.…”
Section: Drone Corridor Reflector Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…• Objective Function: The objective of the process is to find the IRS-ASA pairs that maximizes the average rates throughout the drone corridor, where ξ is the cardinality of ASA set, [U], and R u,µ is the channel rate from (5), achieved when all the IRSs in subset-µ serve the u th ASA. A higher s max yields increased computational complexity; however, this is not a concern as the optimization process runs offline and the IRSs are placed only once.…”
Section: Drone Corridor Reflector Placementmentioning
confidence: 99%
“…Optimal placement of BSs has been studied with several different performance criteria in the literature, such as cost, coverage, and capacity [4,5]. The optimal placement of reflectors is also studied with similar motivations.…”
Section: Introductionmentioning
confidence: 99%
“…In [37], authors have reported the application of a deep learning based approach to model path loss on fixed wireless access techniques in suburban scenarios. In [38] and [39], learning aided approaches for proper utilization of the UAV channel have been reported. Despite the reported use of several learning based approaches for UAV channel modeling, there are opportunities for obtaining performance improvements and optimal computation if the input feed mechanisms are expanded with tapped delay line (TDL) [31], [32] blocks and configuring gated functions in innovative combinations to facilitate detailed feature learning, missing content recovery, tracking time variations and preserving context of the processed content.…”
Section: A Related Workmentioning
confidence: 99%
“…So the recovery of x 1 from y R1 is related to the consideration of x 2 as an interference signal. Using (37) and (38),…”
Section: G Application In a Mimo-noma Set-upmentioning
confidence: 99%
“…Optimal placement of BSs has been studied with several different performance criteria in the literature, such as cost, coverage, and capacity [4], [5].…”
Section: Introductionmentioning
confidence: 99%